Evaluasi Evaluasi Kelayakan Mutu Ruang Tahanan Di Satuan Kewilayahan Dalam Rangka Peningkatan Kualitas Pelayanan Publik Berbasis Hak Asasi Manusia: Evaluasi Kelayakan Mutu Ruang Tahanan Di Satuan Kewilayahan Dalam Rangka Peningkatan Kualitas Pelayanan Publik Berbasis Hak Asasi Manusia - Harvin Raslin (Jurnal Litbang Polri, 2023)
Based on a phenomenon that the feasibility of the quality of the detention room is still a problem, one of which is in the aspect of the appropriateness of the quality of the detention room, especially regarding security and safety. Taking the example of the fire that occurred at the Class I Penitentiary (Lapas) Tangerang (tribunnews.com, September 8, 2021) where 122 detainees lived and killed 49 detainees during the fire, is a phenomenon that occurred in the detention room. This study uses a mixed-method approach, namely a combination of quantitative methods and qualitative methods. This approach is intended to obtain input data that is different from the collection technique for the sharpness of data analysis. This mixed-method contains elaboration of questions that focus on fulfilling human rights standards in 2 (two) aspects, namely the feasibility of the quality of the detention room building and the quality of public service facilities in the detention room. Based on the discussion and results of the analysis, it can be concluded that overall the condition of the Polri detention rooms in 11 Polda areas is still in a decent condition where the presence of CCTV in the detention room and drinking water facilities in the detention room are a public service facility for the detention room in a decent condition. The recommendations obtained from this research are 1). The need for improvement regarding the height of the ceiling and ventilation which must be safe from the reach of prisoners, 2). there needs to be technological innovation in intelligent detention rooms to improve public services, 3). There needs to be an additional temporary room for drug prisoners and a separate room for infectious disease prisoners, 4). there must be a separate detention room that can be used multi-functionally within the framework of providing guarantees for the protection of detainees' human rights.